(untitled) (Docentes 2.0 Journal, 2026)
Financial literacy has become a fundamental component of holistic education for young people, particularly in contexts where economic decision-making is increasingly complex. The objective of this research was to analyze the perspectives of technical high school students specializing in accounting regarding financial literacy at the Sara Serrano de Maridueña Educational Unit in Ecuador. The study was framed within the sociocritical paradigm, employing an interpretive method, a qualitative approach, an interpretive phenomenological design, and a cross-sectional scope. The sample consisted of 12 students who participated in semi-structured interviews to explore their experiences and perceptions of the financial education they received during their academic training. The results revealed that although a curricular foundation in the subject exists, students have limited knowledge of key aspects such as saving, budgeting, and investing. Furthermore, a gap was evident between the theoretical content covered in the curriculum and its practical application in daily life. It was concluded that strengthening the integration of financial literacy into educational processes requires pedagogical strategies that bridge theory and practice, thereby developing students’ financial competencies.